Cryptofavognathus, a new genus of the family Cryptognathidae Oudemans (Acari: Raphignathoidea), with the description of a new species from Turkey - Doğan, Sali̇h; Dönel, Güldem (Zootaxa, 2010)
A new genus, Cryptofavognathus is proposed for two species, Cryptofavognathus afyonensis (Koç & Akyol, 2004) comb. nov. and C. anatolicus sp. nov. The adult female and male of C. anatolicus sp. nov. collected from moss and a bird’s nest are herein described and figured.